The Green and Digital Twin Transition: EU vs US Firms - Reinhilde Veugelers; Clémence Faivre; Désirée Rückert; Christoph Weiss (Intereconomics, 2023)
Using new and unique survey evidence on digitalisation activities and investment in climate change of non-financial firms in the EU and the US, this article documents the trend towards twin digital and green investment in the corporate landscape after the COVID-19 pandemic. We use information from the 2021 European Investment Bank Investment Survey on firms' use of advanced digital technologies and their investments to tackle physical and transition risks from climate change. We show that a substantial share of firms is not implementing any state-of-the art digital technologies, has not invested to tackle climate change, and furthermore has no plans to invest in the near future. At the same time, numerous firms have made the twin transition by investing in both digitalisation and environmental sustainability and plan to further increase their investments post-COVID-19. Comparing EU and US firms, the pandemic did not help to bridge the digital gap between the EU and the US, with European firms more likely to be stuck on the wrong side of the digitalisation divide. Still, they are more likely to be leading on green investment, including on twinning green and digital technologies.
Keywords: D22; M15; M20; O33; 330; company; climate change; environmental protection investment; digitalization; EU countries; USA; Unternehmen; Klimawandel; Umweltschutzinvestition; Digitalisierung; EU-Staaten; USA